2008
DOI: 10.1091/mbc.e07-09-0870
|View full text |Cite
|
Sign up to set email alerts
|

A Motif in the Clathrin Heavy Chain Required for the Hsc70/Auxilin Uncoating Reaction

Abstract: The 70-kDa heat-shock cognate protein (Hsc70) chaperone is an ATP-dependent "disassembly enzyme" for many subcellular structures, including clathrin-coated vesicles where it functions as an uncoating ATPase. Hsc70, and its cochaperone auxilin together catalyze coat disassembly. Like other members of the Hsp70 chaperone family, it is thought that ATP-bound Hsc70 recognizes the clathrin triskelion through an unfolded exposed hydrophobic segment. The best candidate is the unstructured C terminus (residues 1631-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 46 publications
1
78
0
3
Order By: Relevance
“…1b), near known binding sites of auxilin and Hsc70 (20). Furthermore, a C-terminal clathrin heavy chain mutation, or truncation, resulted in defective coat disassembly (18,20). Two observations suggest that HRY54 CHC1-GFP forms functional CCVs, in vivo.…”
Section: Resultsmentioning
confidence: 98%
“…1b), near known binding sites of auxilin and Hsc70 (20). Furthermore, a C-terminal clathrin heavy chain mutation, or truncation, resulted in defective coat disassembly (18,20). Two observations suggest that HRY54 CHC1-GFP forms functional CCVs, in vivo.…”
Section: Resultsmentioning
confidence: 98%
“…It has also been shown that approximately three molecules of Hsc70 dissociate one triskelion when coated vesicles rather than empty cages were used (6) and it has been found that, following disassembly, three Hsc70s are bound to each free triskelion (14,15). Identification of the Hsc70 binding motif and the location of this within the cage structure suggest that Hsc70 can bind to three potential binding sites on flexible regions protruding down from the hub (27).…”
Section: Discussionmentioning
confidence: 99%
“…1) (Fotin et al 2004b). The carboxy-terminal segment contains a short region with an amino acid sequence that is preferentially recognized by Hsc70 and required for Hsc70-facilitated uncoating (Rapoport et al 2008;Böcking et al 2011). The 42 zig-zags that make up the bulk of the polypeptide chain create an extended, gently curved "leg" for the clathrin triskelion (from the Greek for "a three-legged structure"), with the b-propeller "terminal domain" at its tip.…”
Section: Clathrinmentioning
confidence: 99%
“…Within the clathrin carboxy-terminal segment is a short, hydrophobic sequence, necessary for Hsc70-and ATP-dependent uncoating and very similar to an optimal Hsc70-interacting peptide (Rapoport et al 2008). Auxilin associates with a clathrin lattice in such a way that an Hsc70 molecule, recruited by the J-domain, can, in turn, bind a nearby clathrin carboxyterminal segment (Fig.…”
Section: Uncoatingmentioning
confidence: 99%